DAMPAK EKSPLOITASI HUTAN DI FILIPINA TERHADAP KEHIDUPAN MASYARAKAT DAN LINGKUNGAN - Sudiyono Sudiyono (Jurnal Masyarakat dan Budaya, 2008)
The Philippines is one of the largest archipelagic states on the world. Its lies near the equator and underneath its islands, lies the tectonic plates, which has made the country vulnerable to natural disasters. These include tropical storms, floods, droughts, tidal waves, tornadoes, land slides, earthquakes, tsunami and volcanic eruptions. Not all natural disaster has been caused by natural factor. For example, wide spread droughts disaster in the Philippines area, are not merely an El-Nino fenomenon; it also due to an external factor such as the aggravation of the ecological problem. The length and the severity of dry seasons, derives also from the lack forest cover. In other words, it is also a man-made natural disaster, especially the extensive legal and illegal logging activities, which rampant in the Philippines country. From this study we can understand that environmental problems involve many aspects such as social, politic, and economic.